Broadcasting Ourselves: Opportunities for Researchers to Share Their Work Through Online Video - Smith, Adrian A. (Frontiers in Environmental Science, 2020)
For researchers, producing and publishing online video can be a means of directly sharing both our science and ourselves with a wide audience. However, media production often requires a substantial commitment of time, effort, and resources. Beyond this, publishing video on popular online platforms, like YouTube, is entering an ever-more crowded information marketplace. At the outset, considering the stories and distribution avenues specifically available to research scientists can guide their efforts in media production. In this practical perspective piece, I speak to a scenario of when media production is led or self-produced by a research scientist wanting to communicate their work. I present how research scientists have opportunities and access to stories that are rare among other professionals communicating science online. From disseminating the results of a peer-reviewed research paper, to making media about typically unseen aspects of science, online video is a medium that presents unique opportunities for researchers wanting to communicate their work. It can be a means of expanding the audience for and our own conceptions of scholarly work.